Bringing Planctomycetes into pure culture - Lage, Olga M.; Bondoso, Joana (Frontiers in Microbiology, 2012)
Planctomycetes have been known since the description of Planctomyces bekefii by Gimesi at the beginning of the twentieth century (1924), although the first axenic cultures were only obtained in the 1970s. Since then, 11 genera with 14 species have been validly named and five candidatus genera belonging to the anaerobic ammonium oxidation, anammox bacteria have also been discovered. However, Planctomycetes diversity is much broader than these numbers indicate, as shown by environmental molecular studies. In recent years, the authors have attempted to isolate and cultivate additional strains of Planctomycetes. This paper provides a summary of the isolation work that was carried out to obtain in pure culture Planctomycetes from several environmental sources. The following strains of planctomycetes have been successfully isolated: two freshwater strains from the sediments of an aquarium, which were described as a new genus and species, Aquisphaera giovannonii; several Rhodopirellula strains from the sediments of a water treatment recycling tank of a marine fish farm; and more than 140 planctomycetes from the biofilm community of macroalgae. This collection comprises several novel taxa that are being characterized and described. Improvements in the isolation methodology were made in order to optimize and enlarge the number of Planctomycetes isolated from the macroalgae. The existence of an intimate and an important relationship between planctomycetes and macroalgae reported before by molecular studies is therefore supported by culture-dependent methods.